Jørgen Leth - Film Portraits, Disc 3 - Leth, Jorgen; Roos, Peter; Salomon, Mikael; Holmberg, Dan; Ringholm, Carsten (Danish Film Institute, 2008)
Leth's "Kalule" (1979) is a portrait of the Ugandan boxer Ayub Kalule who lived in Denmark in the 1970s. The film tracks his rise to the world championship titles that made him such a huge star in his adopted homeland. In "Michael Laudrup - A Football Player" (1993), Leth catches Michael Laudrup, arguably Denmark's best footballer ever, at the peak of his form, as a key player on one of the world's best teams, FC Barcelona. We hear Laudrup discuss the game of football and the team that gave him ideal opportunities to unfold his talent. All the while, Leth keeps his focus squarely on Laudrup, the football artiste, tightly framed in games and on the practice pitch, highlighting Laudrup’s nearly ballet-like movement patterns, his virtuosic ball-handling and superior eye for the game. [www.dfi.dk]
Keywords: DVD-Video